Management of Light for Quality Production of Litchi - Purbey, Sushil Kumar; Singh, Sanjay Kumar; Pongener, Alemwati (International Journal of Bio-resource and Stress Management, 2019)
Light is prerequisite for plant growth and production of quality fruit. Management of different aspects of light viz. quantity, quality and duration promises to provide a new technological alternative to sustainable production of horticultural crops. Litchi is very sensitive to climatic aberrations. The growth, panicle emergence time, flowering behavior, yield and quality of fruits have been found to be influenced by the impact of climate change. Under changing climatic conditions and consumer’s demand, light can be managed by pruning and training, bagging of fruit bunches, use of photo-selective shade nets and reflective films in orchards. These concepts, involved in optimization of light quantity and quality, have significant effect on the litchi tree responses and practically feasible tools for sustainable management of yield and quality in modern litchi orchards. Canopy management in litchi improves the ability of sunlight to penetrate the tree, enhances the colour of fruit and improves quality. Pruning resulted in increased photosynthetic efficiency of litchi plants due to improved light penetration inside the trees. Similarly bagging of fruit bunches and use of shade net has been reported to produce more class-I fruit by reducing incidences of sun-burn and cracking of fruits. This review attempts to bring together research on effect of light on fruit quality and how manipulation of light can be achieved through different practices in the orchard towards quality fruit production under changing climatic conditions.